2017
DOI: 10.1111/hcre.12123
|View full text |Cite
|
Sign up to set email alerts
|

When News Meets the Audience: How Audience Feedback Online Affects News Production and Consumption

Abstract: Innovations in communication technology have changed the way news is produced and consumed. Various digital platforms, ranging from news websites to social media sites to personal blogs, have enabled news users to indicate how much they like the news they have read, to share it with others, and to leave comments. News users' mouse clicks are automatically recorded and aggregated by computational systems and made publicly visible (e.g., “Most Read Articles”). This essay reviews the ever‐growing research on how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(108 citation statements)
references
References 44 publications
2
100
0
6
Order By: Relevance
“…Where once media could be criticized for failing to adjudicate the truth (Pingree, Brossard, & McLeod, 2014), many news outlets, especially those on the far right and left, now actively construct the "truth" to align with their partisan leanings. The media's power has become decentralized, with political blogs' content and audiences' search patterns helping to set the news agenda (Gruszczynski & Wagner, 2016;Lee & Tandoc, 2017). As the media system and content has evolved, the nature of media audiences has changed as well.…”
Section: An Early 21st-century Communication Ecologymentioning
confidence: 99%
“…Where once media could be criticized for failing to adjudicate the truth (Pingree, Brossard, & McLeod, 2014), many news outlets, especially those on the far right and left, now actively construct the "truth" to align with their partisan leanings. The media's power has become decentralized, with political blogs' content and audiences' search patterns helping to set the news agenda (Gruszczynski & Wagner, 2016;Lee & Tandoc, 2017). As the media system and content has evolved, the nature of media audiences has changed as well.…”
Section: An Early 21st-century Communication Ecologymentioning
confidence: 99%
“…The two‐step flow of communication model (Katz & Lazarsfeld, ) proposed that there are intervening variables such as recipients' predispositions (e.g., prevailing prejudices) or communication with peers that qualify the actual effect of mass media on recipients' views. Even beyond this notion, the unidirectional influence of media coverage on recipients' opinions has been questioned, alternatives proposing that audiences themselves exert impact on media determining which topics and stances media institutions cover in their reports (e.g., Glynn, Herbst, Lindeman, O'Keefe, & Shapiro, ; see Lee & Tandoc, ).…”
Section: The Formation Of Opinion Climates Through the Lens Of Mass Amentioning
confidence: 99%
“…Research has also demonstrated social influence effects when considering cues that are emblematic of diminished message control. For example, online news site readers favor popular content that is recommended by others (Yang, ) and they spend more time reading online news articles that prior readers rated positively (Knobloch‐Westerwick, Sharma, Hansen, & Alter, ; see also Lee & Tandoc, ). Also, online news articles with greater Facebook “likes” have been shown to be clicked on more frequently, selected earlier, and read for longer than articles with a low number of likes, particularly when impression motivations are high and people are inspired to appear likeable and develop positive relationships with unknown others (Winter, Metzger, & Flanagin, ).…”
Section: Social Influence Processes In An Environment Of Mass and Intmentioning
confidence: 99%